EXECUTION OF DEATH PENALTY IN NARCOTICS CRIME IN THE PERSPECTIVE OF NATIONAL LAW IN INDONESIA - Muhammad Nasir Sitompul; Ariman Sitompul (International Asia Of Law and Money Laundering (IAML), 2022)
The abuse of illegal drugs is a threat to the sovereignty of the nation and the state of drug eradication requires the role of all parties to narrow the movement of drug dealers who are still trying to market the illicit goods in indonesia. The regulation on narcotics crime and death penalty is very important in regulating the law for the perpetrators of narcotics crime for the sake of national and state sovereignty.In Indonesia today, the imposition of criminal sanctions in the form of a death penalty by a judge for perpetrators of narcotics is one of the policies adopted in Law No. 35 of 2009 on narcotics and cannot be separated from the criminal law norms adopted by the criminal law so far, for example in Article 10 of the Criminal Code. Another thing in the other world is that there is a significant development of narcotics users by taking depenalization actions against users that aim to replace prison sanctions that are sometimes applied to other criminal sanctions such as Social Work sanctions. The research method used is juridical empirical meaning is to identify and conceptualize the law as a real and functional social institution in a patterned living system.